The Art of Process Improvement in Operations Management: Delve into The Art and Science of Improving Processes to Achieve Operational Excellence - Ghutke, Pratik C.; Uma Yadav, Dishimukh; Tekade, Atul (Journal of Neonatal Surgery, 2025)
At the core of operational excellence lies process improvement, enabling organizations to enhance efficiency, cut expenses, and provide exceptional customer value. This article delves into the multifaceted realm of process improvement, examining innovative approaches like Lean Manufacturing, Six Sigma, Total Quality Management (TQM), and Business Process Reengineering (BPR). By combining theoretical knowledge, practical applications, and success stories from the real world, this research demonstrates how companies can leverage process enhancements to achieve remarkable outcomes. The study also tackles obstacles such as change resistance, leadership's influence, and the incorporation of state-of-the-art technologies. Process improvement has emerged as a potent catalyst for innovation and expansion by merging technical accuracy with creative problem-solving.